1993
DOI: 10.1128/iai.61.6.2513-2519.1993
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane protein YadA of enteropathogenic yersiniae mediates specific binding to cellular but not plasma fibronectin

Abstract: The binding of bacteria or bacterial products to host proteins of tissue extracellular matrix may be a mechanism of tissue adherence. We investigated interactions of the plasmid-encoded outer membrane protein YadA, which confers pathogenic functions on enteropathogenic yersiniae, with fibronectin. Attachment of YadA-positive and YadA-negative recombinant Yersinia enterocolitica strains to cartilage-derived human cellular fibronectin and human plasma fibronectin in the solid phase revealed that YadA mediates bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…Further study of YadA binding using human cellular fibronectin and human plasma fibronectin revealed that only the former bound YadA. The simplest explanation is that the YadAbinding site in fibronectin is not present in the plasma variant of this protein (Schulze-Koops et al, 1993). Now, YadA is a virulence factor of Y. enterocolitica, but is dispensable for the virulence of Y. pseudotuberculosis, and in wild-type Y. pestis, the yadA gene has a frameshift mutation silencing the gene.…”
Section: Bartonella Henselaementioning
confidence: 99%
“…Further study of YadA binding using human cellular fibronectin and human plasma fibronectin revealed that only the former bound YadA. The simplest explanation is that the YadAbinding site in fibronectin is not present in the plasma variant of this protein (Schulze-Koops et al, 1993). Now, YadA is a virulence factor of Y. enterocolitica, but is dispensable for the virulence of Y. pseudotuberculosis, and in wild-type Y. pestis, the yadA gene has a frameshift mutation silencing the gene.…”
Section: Bartonella Henselaementioning
confidence: 99%
“…The second functional motif is two proline-rich regions; one lying immediately adjacent to the RGD motif and the other within the C-terminal region of the protein (Emsley et al, 1996). These sites may provide rapid (though weak), nonstoichiometric binding sites that are functionally (Roggenkamp et al, 1996) Extracellular matrix proteins (Emody et al, 1989;Schulzekoops et al, 1992Schulzekoops et al, , 1993 Protects against complement and defensin lysis (Balligand et al, 1985;Pilz et al, 1992;Flugel et al, 1994) Autoaggregation (Skurnik et al, 1984) important (Williamson, 1994). Other autotransporter proteins also possess loops extending from the predicted b-helix structure, which may incorporate uncharacterized functional motifs.…”
Section: Structure Of the Passenger Domainmentioning
confidence: 99%
“…YadA mediates bacterial adherence to various types of collagen (Embdy et al, 1989;Schulze-Koops et al, 1992) as well as to fibronectin (Tertti et ai, 1992;Schulze-Koops et al, 1993). We assessed the E. coli C600 strains (expressing the wild-type YadAveos and YadAYeo3 .\83-io4) for adherence to various proteins of the extracellular matrix as well as to reconstituted basement membrane immobilized on glass.…”
Section: Binding To Extracellular Matrix Componentsmentioning
confidence: 99%